Biomechanical analysis of lower limbs during stand-to-sit tasks in patients with early-stage knee osteoarthritis - Pan, Jing; Huang, Wenqin; Huang, Zhiguan; Luan, Jun; Zhang, Xiaohui; Liao, Bagen (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Knee osteoarthritis (KOA) is a common degenerative disease among the older people that severely affects their daily life. Previous studies have confirmed that movement biomechanics are altered in patients with KOA during task performance. However, changes that occur in lower limb joints and muscles in the three planes during stand-to-sit (STS) tasks in patients with early-stage KOA are unclear. Method: Of the 36 participants recruited in this study, 24 (8 males and 16 females) and 12 (4 males and 8 females) were added to the KOA and control groups, respectively. The Nexus Vicon motion capture system along with Delsys wireless surface electromyography devices and plantar pressure measurement mat was used to record test data. A Visual 3D software was used to process the data and calculate the biomechanical and electromyographic parameters during STS tasks. Results: There was no significant difference in task duration between the two groups. Patients with KOA could perform a greater range of pelvic motion and smaller range of hip and knee joint motion with a lower maximum hip joint angular acceleration in the sagittal plane and greater knee and ankle joint motion in the coronal plane. There was no significant difference in the motion range in the horizontal plane. During the STS task, patients in the KOA group had a lower vertical ground reaction force (GRF) amplitude on the injured side but a higher integrated GRF on both sides than those in the control group. Moreover, patients with KOA demonstrated higher PERM and PABM of the lower limb joints and smaller knee PADM and ankle PEM. Additionally, maximum activation levels of GMed muscle, affected-side gluteus medius (GM), ST, rectus femoris (RF), and tibialis anterior (TA) muscles were lower in patients with KOA than in controls. Conversely, the activation level of biceps femoris (BF) was higher. Furthermore, the integral EMG values of GMed, GM, ST, VL, RF, vastus medialis VM, and TA muscles on the affected side were lower, except for the BF muscle, in patients with KOA. Conclusion: Compared with the participants in the control group, patients with early-stage KOA exhibited consistent changes in sEMG parameters and biomechanical alterations in the sagittal plane, as observed in previous studies. However, differences in parameters were observed in the coronal and transverse planes of these patients. The noninvasive analysis of the 3D parameters of the involved motion patterns may lead to the early detection of KOA.